Financing the Future : Building an Open, Modern and Inclusive Financial System - Drees-Gross, Alexandra; Annamalai, Nagavalli; Wong, Sau Ngan; Htay, Nang Htay; De Luna Martinez, Jose; Tanaka, Kiyotaka; Natarajan, Harish; Mahadevan, Balakrishnan; Mortimer-Schutts, Ivan (World Bank, Yangon, 2016)
Myanmar’s financial system is undergoing a rapid transformation. A history of economic isolation has left Myanmar with small and underdeveloped financial institutions and very low access to financial services. Since 2011, however, demands on the financial system have grown exponentially with increased trade and investment, growing household income, and expanding government operations. While recent reforms have stimulated financial sector growth, much more needs to be done to establish a competitive and vibrant financial sector that can meet the needs of Myanmar’s expanding economy, boost incomes, and reduce poverty particularly among those living in rural areas. Increasing access to financial services is critical to achieving shared prosperity in Myanmar.